2021
DOI: 10.1111/jce.14987
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrosis and substrate based characterization in atrial fibrillation: Time to move forwards

Abstract: Atrial fibrillation (AF) is the most commonly encountered cardiac arrhythmia in clinical practice. However, current therapeutic interventions for atrial fibrillation have limited clinical efficacy as a consequence of major knowledge gaps in the mechanisms sustaining atrial fibrillation. From a mechanistic perspective, there is increasing evidence that atrial fibrosis plays a central role in the maintenance and perpetuation of atrial fibrillation. Electrophysiologically, atrial fibrosis results in alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 154 publications
(184 reference statements)
0
11
0
1
Order By: Relevance
“…As a consequence, excessive extracellular matrix deposition and cardiac fibrosis exacerbated AF and triggered the recurrence of AF after RFA. 32 Emerging evidence demonstrated that TCF21 polymorphism plays an important role in cancer, 22,23 coronary artery diseases 16,17 and ventricular septal defects. 18 For instance, the CG and GG genotypes of rs12190287 predict elevated risk of osteosarcoma 23 and conferred genetic susceptibility to VSDs in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, excessive extracellular matrix deposition and cardiac fibrosis exacerbated AF and triggered the recurrence of AF after RFA. 32 Emerging evidence demonstrated that TCF21 polymorphism plays an important role in cancer, 22,23 coronary artery diseases 16,17 and ventricular septal defects. 18 For instance, the CG and GG genotypes of rs12190287 predict elevated risk of osteosarcoma 23 and conferred genetic susceptibility to VSDs in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…[38] The structural remodeling of atrial fibrosis theoretically leads to a decrease in muscle fiber activation, which affects the FWA voltage. [39,40] Therefore, lower FWA in lead V 1 implies a reduction in right atrial voltage with increased low voltage areas as a result of advanced structural remodeling with progression of AF.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy could be reconciled by considering that PS formation most likely occurs as a consequence of tissue micro‐structural heterogeneities in combination with dynamic functional factors 44 . According to this idea, areas of local hotspot concentration could be hypothesized to be occurring via the effect of relatively fixed heterogeneities in the myocardium caused by areas of micro‐fibrosis 45 . On the other hand, many and perhaps, most, PSs occur as a consequence of dynamic alterations in tissue conduction and refractoriness.…”
Section: Discussionmentioning
confidence: 99%